Adolescent Pregnancy and Child Marriage: Current Situation in Indonesia - Aladin, Aladin (Andalas Obstetrics And Gynecology Journal, 2023)
Adolescent pregnancy and child marriage is a common public health problem worldwide.  It is one of the key issues concerning reproductive health of women not only in developing countries but also in developed countries, including Indonesia.  The international community is also aware that the problem of Adolescent pregnancy and child marriage is a very serious problem. The general implication is that women and children will be at risk in various aspects, related to unwanted marriages, forced sexual intercourse, pregnancy at a very young age, as well as an increased risk of transmission of HIV infection, other sexually transmitted diseases, and cervical cancer. The purpose of the article is to review current situation and issues on adolescent pregnancy and child marriage in Indonesia.